Spatiotemporal Localization of d-Amino Acid Oxidase and d-Aspartate Oxidases during Development in Caenorhabditis elegans - Saitoh, Yasuaki (American Society for Microbiology, 2012)
Recent investigations have shown that a variety of d-amino acids are present in living organisms and that they possibly play important roles in physiological functions in the body. d-Amino acid oxidase (DAO) and d-aspartate oxidase (DDO) are degradative enzymes stereospecific for d-amino acids. They have been identified in various organisms, including mammals and the nematode Caenorhabditis elegans, although the significance of these enzymes and the relevant functions of d-amino acids remain to be elucidated. In this study, we investigated the spatiotemporal localization of C. elegans DAO and DDOs (DDO-1, DDO-2, and DDO-3) and measured the levels of several d- and l-amino acids in wild-type C. elegans and four mutants in which each gene for DAO and the DDOs was partially deleted and thereby inactivated. Furthermore, several phenotypes of these mutant strains were characterized. The results reported in this study indicate that C. elegans DAO and DDOs are involved in egg-laying events and the early development of C. elegans. In particular, DDOs appear to play important roles in the development and maturation of germ cells. This work provides novel and useful insights into the physiological functions of these enzymes and d-amino acids in multicellular organisms.